The Hazards of Role Modelling for the Education of Moral and/or Virtuous Character - Carr, David (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2023)
In contrast to both behaviourist and cognitive approaches to moral development, neo-Aristotelian virtue ethics has had recent fairly distinctive impact on thought about the practice of moral education. On this view, insofar as moral development is a matter of the cultivation of moral virtues, and virtues are basically qualities of character conducive to good or admirable conduct, virtue formation is reducible neither to behaviour training nor to (mere) intellectual acquaintance with knowledge or principles, and requires essentially practical initiation into the distinctive (Aristotelian) moral wisdom of phronesis. In turn, such focus on the cultivation of practical wisdom has led to large emphasis on the contribution of moral exemplars and role modelling for the moral education of (particularly) young people. This paper argues that such emphasis is seriously overstated, if not wholly misplaced, and that role modelling and exemplification can have only a secondary place at best in any reputable moral educational project or program.